2019
DOI: 10.1063/1.5079818
|View full text |Cite
|
Sign up to set email alerts
|

The thickness and growth temperature dependences of soft magnetic properties and an effective damping parameter of (FeCo)-Si alloy thin films

Abstract: The dependences of magnetic properties and effective damping parameter (αeff) on film-thickness (d) and growth temperature (Ts) for Fe69Co26Si5 alloy films are investigated. The saturation magnetization (Ms) are found to decrease from approximately 1,700 to 1,500 emu/cm3 with d for Ts = 230 °C. For 40 nm films, the magnetization remains constant over the entire range of Ts from 35 to 360 °C. The coercivity (Hc) values for Ts above 120 °C are approximately 20 Oe. Those films deposited at Ts =120 °C or higher ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In angular dependent FMR measurements, minima of the resonance field indicate an easy axis, whereas maxima correspond to hard axes. Therefore, the easy axes of the four-fold anisotropy are along the 100 directions of Fe 69 Co 26 Si 5 , consistent with the quasi-static magnetic properties, see figure 2 and reference 10 . Close inspection of the difference of the residual using a purely four-fold fit, i.e.…”
Section: Fmr Measurement Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…In angular dependent FMR measurements, minima of the resonance field indicate an easy axis, whereas maxima correspond to hard axes. Therefore, the easy axes of the four-fold anisotropy are along the 100 directions of Fe 69 Co 26 Si 5 , consistent with the quasi-static magnetic properties, see figure 2 and reference 10 . Close inspection of the difference of the residual using a purely four-fold fit, i.e.…”
Section: Fmr Measurement Resultssupporting
confidence: 79%
“…The quasi-static and dynamic magnetic properties of Fe 69 Co 26 Si 5 alloy thin films of various thicknesses were studied using VSM and broadband FMR. The quasistatic magnetic properties such as saturation magnetization, coercivity and the remanence to saturation magnetization ratio all show only a weak thickness dependence, for more details see reference 10 . The dynamic measurements using broadband FMR and in-plane angle dependent measurements unambiguously show that [100] and [110] are the easy and hard axes respectively of the dominant four-fold anisotropy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Himalay Basumatary et al, studied the effect of deposition temperature on the magnetic properties of FeGa thin films and found that high temperature deposition can greatly reduce the coercivity, since high temperature deposition could be a feasible method to improve the soft magnetic properties of thin films [ 20 ]. There exist some studies on the effects of high temperature deposition on the magnetic properties of FeCo-based alloy thin films [ 21 , 22 , 23 , 24 ]. However, the relationships between structure and magnetic properties have not yet been systematically studied.…”
Section: Introductionmentioning
confidence: 99%